Forensic psychiatric analysis of organic personality disorders after craniocerebral injury in Shanghai, China - Li, Beixu; Fang, Youxin; Lin, Junyi; Chen, Xueyan; Li, Chenhu; He, Meng (Frontiers in Psychiatry, 2022)
Objective: To explore the incidence rate and the differences of clinical manifestations of organic personality disorders with varying degrees of craniocerebral trauma. Materials and Methods: According to the International Classification of Diseases-10, 1027 subjects with craniocerebral trauma caused by traffic accidents were reviewed, the degrees of craniocerebral trauma were graded and those with personality disorder after craniocerebral trauma were diagnosed. The personality characteristics of all patients were evaluated by using the simplified Neuroticism Extraversion Openness Five-Factor Inventory (NEO-FFI). Results: The incidence rate of organic personality disorder after all kinds of craniocerebral trauma was 33.1%, while it was 38.7% and 44.2% in the patients after moderate and severe craniocerebral trauma respectively, which was significantly higher than that in the patients after mild craniocerebral trauma (18.0%) (P<0.05). Compared with the patients without personality disorder, the neuroticism, extraversion and agreeableness scores all showed significantly differences (P<0.05) in the patients with personality disorder after craniocerebral trauma; especially the conscientiousness scores showed significant differences (P<0.05) in the patients with personality disorder after moderate and severe craniocerebral trauma. The agreeableness and conscientiousness scores in the patients with personality disorder after moderate and severe craniocerebral trauma were significantly lower than that after mild craniocerebral trauma, and the patients with personality disorder after severe craniocerebral trauma had lower scores in extraversion than that after mild craniocerebral trauma. Conclusion: The severity and area of craniocerebral trauma is closely related to the incidence rate of organic personality disorder, and it also affects the clinical manifestations of the latter, which provides a certain significance and help for forensic psychiatric appraisal.